Penerapan Etika Administrasi Siswa Berbudaya Positif Dalam Meningkatkan Kualitas Pendidikan di SD Negeri Panorama Kecamatan Cidaun Kabupaten Cianjur - Muchtar, Hendi Suhendraya; Handayani, Sri; Royani, Ida; Supriatna, Supriatna; Sukaenah, Sukaenah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: The aim of this research is to examine and find out empirically about the application of administrative ethics and the implementation of positive school culture and their influence in improving the quality of education at SDN Panorama, Cidaun District, Cianjur Regency. In general, this research aims to analyze and describe the role of administrative ethics and positive culture in improving the quality of education at SDN Panorama. In this research, the author used a qualitative descriptive approach. The research methods are observation, interviews and documentation. Data collection is the recording of events, information and matters relating to some or all elements of the population that will support the research. The results of the research show that the aspects of educational administration and the implementation of positive culture at SDN Panorama have gone very well. It is proven that all SDN Panorama students have good character and personality as a result of several programs supporting the implementation of positive culture. In the organizational aspect that supports the implementation of student administration ethics with a positive culture, all teachers, committee members and parents of students are united in supporting the positive culture program implemented in the school. In the collaborative aspect of implementing positive culture, teachers are at the forefront providing role models and examples of positive discipline habits. The school committee and parents also support this by implementing good habits at school in the family environment in everyday life. With the active role of all school members, the implementation of administrative ethics for students with a positive culture can run well. Keywords: Administrative Ethics, Positive Culture, Educational Administration Abstrak: Tujuan penelitian ini adalah untuk mengkaji dan menemukan secara empiris tentang penerapan etika administrasi dan penerapan budaya positif sekolah serta pengaruhnya dalam meningkatkan kualitas pendidikan di SDN Panorama Kecamatan Cidaun Kabupaten Cianjur. Secara umum penelitian ini bertujuan untuk menganalisis dan mendeskripsikan peran etika administrasi dan budaya positif dalam meningkatkan kualitas pendidikan di SDN Panorama. Dalam penelitian ini, penulis menggunakan pendekatan deskriptif kualitatif. Adapun metode penelitiannyaÂ  adalah observasi, wawancara dan dokumentasi. Pengumpulan data adalah pencatatan peristiwa-peristiwa, keterangan-keterangan, dan hal-hal yang berkaitan dengan sebagian atau seluruh elemen populasi yang akan mendukung penelitian tersebut. Hasil penelitian menunjukan dalam aspek administrasi pendidikan dan penerapan budaya positif di SDN Panorama telah berjalan sangat baik. Terbukti seluruh peserta didik SDN Panorama mempunyai karakter dan kepribadian baik imbas dari beberapa program pendukung penerapan budaya positif. Dalam aspek pengorganisasian yang mendukung penerapan etika administrasi siswa berbudaya positif semua guru, jajaran komite, orang tua peserta didik kompak mendukung program budaya positif yang diterapkan di sekolah. Dalam aspek kolaborasi penerapan budaya positif, guru-guru menjadi yang terdepan memberikan teladan dan contoh-contoh pemebiasaan disiplin yang positif. Komite sekolah dan orang tua ikut mendukung dengan cara pembiasaan yang baik disekolah diterapkan pula di lingkungan kelurga dalam kehidupan sehari-hari. Dengan peran aktif semua warga sekolah penerapan etika administrasi siswa berbudaya positif dapat berjalan dengan baik. Â Kata Kunci: Etika Administrasi, Budaya Positif, Administrasi Pendidikan.